2016
DOI: 10.1590/0074-02760150330
|View full text |Cite
|
Sign up to set email alerts
|

Association of human papillomavirus and Chlamydia trachomatis with intraepithelial alterations in cervix samples

Abstract: The influence of different infectious agents and their association with human papillomavirus (HPV) in cervical carcinogenesis have not been completely elucidated. This study describes the association between cytological changes in cervical epithelium and the detection of the most relevant aetiological agents of sexually transmitted diseases. Samples collected from 169 patients were evaluated by conventional cytology followed by molecular analysis to detect HPV DNA, Chlamydia trachomatis, herpes simplex virus 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
2
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 32 publications
(34 reference statements)
3
21
2
7
Order By: Relevance
“…A larger sample and longitudinal observations would be advantageous for a more accurate conclusion. In Brazil, Wohlmeister et al found, in 2016, a lower prevalence of NG (1.2%), CT (9.5%), and TV (4.7%) than we did [ 21 ]. Nevertheless, in the same country, but 4 years before, de Abreu et al (2016) found higher rates (NG 4.7%, CT 10.3%, and TV 11.6%) [ 22 ].…”
Section: Discussioncontrasting
confidence: 76%
“…A larger sample and longitudinal observations would be advantageous for a more accurate conclusion. In Brazil, Wohlmeister et al found, in 2016, a lower prevalence of NG (1.2%), CT (9.5%), and TV (4.7%) than we did [ 21 ]. Nevertheless, in the same country, but 4 years before, de Abreu et al (2016) found higher rates (NG 4.7%, CT 10.3%, and TV 11.6%) [ 22 ].…”
Section: Discussioncontrasting
confidence: 76%
“…When assessing the association between hr-HPV and individual STIs, there was a significant positive association between hr-HPV and NG and CT. The strong association between HPV infection and STIs has been demonstrated in previous studies, where infection with hr-HPV types, was a risk factor for CT and NG infection [6466]. These findings are significantly of high importance for policy and prevention programmes to include HPV infection in the existing STIs prevention programmes in the country.…”
Section: Discussionsupporting
confidence: 57%
“…HPV infection may have transient symptoms, and spontaneous clearance occurs in 80% of cases as the virus is flushed by the host immune system without any cell changes. In approximately 20% of women, HPV infection may be persistent and later evolve into cervical cancer in up to 10% of cases (Abreu et al, 2012;Wohlmeister et al, 2016). Actually, the most important viral factor is the type of HPV.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that the most common HR HPV detected in carcinoma cases are HPV 16, 18, 31, 33, 39, and 45 (Muñoz 2000;Kraus et al, 2006;Parkin et al, 2008;Wohlmeister et al, 2016a). Kaliff et al, ( 2018) carried out a study and found that HPV 16 was the most prevalent genotype, followed by HPV 18: the two are the main genotypes detected in squamous cell carcinoma (Oliveira-Silva et al, 2011;Wohlmeister et al, 2016). The 12 other high-risk HPV genotypes (viz.,HPV 31,33,35,39,45,51,52,56,58,59,66,and 68) were highly prevalent in the present study; more in fact than HPV 16 or HPV 18.…”
Section: Discussionmentioning
confidence: 99%